Comme une bitch ? Exploration des variations d’usage et de sens entre « bitch » et « chienne » en tant qu’insultes sexistes - Aure Espilondo (Glad!)
This article aims to examine the semantic gap between “chienne” and “bitch” —slurs that conjure up the image of a female dog, yet characterize it in different ways. Evaluating the extent of that gap, by using both conventional and specialized dictionaries, allows us to consider potential semantic evolutions: in the United-States, « bitch » is undergoing a process of positive appropriation driven by its plasticity and by a reevaluation of its connotations. Could “chienne” undergo a similar process in metropolitan France despite its radically different characteristics? This possibility is assessed through a case study on the usage of “chienne” and “bitch” by three French female singers and rappers: Aya Nakamura, Tracy de Sá, and Liza Monet. That study shows that, although there is no current widespread positive usage of the insult “chienne”, its meaning is already being challenged.